Development of a structured interview for the modified version of the Beth Israel Hospital psychosomatic questionnaire for alexithymia - Komaki, Gen; Baba, Takanobu; Yoshida, Toshiyuki; Arimura, Tatsuyuki; Moriguchi, Yoshiya; Maeda, Motonari (Frontiers in Psychiatry, 2024)
Background An observer-rated questionnaire for alexithymia based on the original 17-item Beth Israel Hospital Psychosomatic Questionnaire for Alexithymia (BIQ) was developed by Sifneos in 1973 and modified into a 12-item version of BIQ by Taylor et al. in 1997. However, it has rarely been used in a clinical or research context and studies have not given satisfactory inter-rater reliability for the 12-item version. Objective To develop a structured interview in Japanese for the12-item modified version of BIQ (m-SIBIQ) to determine the reliability and validity of the m- scores and its factor structure model. Methods Ninety-two Japanese young adults were interviewed. The inter-rater reliability of the m-SIBIQ was assessed by exploratory factor analysis. For the concurrent and convergent validities, correlation analysis was done between the scores of m-SIBIQ and the self-reported questionnaires: 20-Item Toronto Alexithymia Scale (TAS-20), NEO Five-Factor Inventory (NEO-FFI), Emotional Empathy Scale (EES), Interpersonal Reactivity Index (IRI), Beck Depression Inventory-II (BDI-II), and State-Trait Anxiety Inventory (STAI). Goodness of fit of the structure model of the m-SIBIQ was evaluated using confirmatory factor analysis, and the results were examined through stepwise multiple regression analysis. Results Good reliability was obtained for the total score of m-SIBIQ: Cronbach’s α.950 (p<.001) and ICC.75(p<.05). The validity of the factor structure was obtained by confirmatory factor analysis using covariance. The model of the alexithymia constructs was configured by the operative thinking (la pensée opératoire) and affect awareness components. The stepwise multiple regression analysis extracted the total score of m-SIBIQ as significantly, negatively correlated with the Openness to experience score of NEO-FFI and significantly, positively correlated with the emotionally chilly score of EES and the score of difficulty describing feelings (DDF) of TAS-20. There were no correlations between the m-SIBIQ and BDI-II scores. Conclusion For Japanese young adults, the m-SIBIQ is a reliable and valid instrument for overcoming weaknesses of the self-reported procedures by bringing to light the alexithymia construct and principal dimensions.